On the issue of creatingthe soil of conservation restrictions when using agricultural land - Kustovska, O.; Polishchuk, O. (Land Management, Cadastre and Land Monitoring, 2020)
The article analyzes the current problems of land management for agricultural land use in Ukraine, because fertile land is the basis of civilized human life, and their condition, to a large extent, reflects the health of any nation. Therefore, the intensive exploitation of land to complete exhaustion without the use of improving measures is a complete environmental suicide. Soil is not only the main condition for the existence of human society, but also the most important source of national wealth, a universal factor in any human activity. In agricultural production, land is the main mode of production, without which the process of manufacturing of crop and livestock production is impossible, is both an object and a means of labor, determines not only the pace of development, but also the level of efficiency of agricultural production.Directions for the formation of soil protection restrictions in the use of agricultural land for lease land use are justified, in particular: agricultural land plots for commercial agricultural production should be used in compliance with the established terms for the return of individual crops in accordance with the permissible types and types of crop rotation according to land management projects, and  also landowners and land users in the implementation of ho  business activities are obliged to inform the executive authorities and local governments on the quality condition, degradation and pollution of land plots, on the sown area of crops grown on them, with the obligatory registration of the relevant changes in the land cadastre.Key words: soil protection, land management projects, crop rotation, soil cultivation, restrictions, land use, crop rotation.